The dynamic relationships of macroeconomic variables and stock index : study of Malaysia and Singapore - Yap, Sarah Siong Yen (Universiti Malaysia Sarawak, (UNIMAS), 2012)
Malaysia and Singapore once used to be under the same ruling and sharing the stock exchange. However, the split of Malaysia and Singapore causes the stock exchange to split too and both countries move into different direction of economic development. Malaysia is known as the Emerging Tiger and Singapore is the Asian Tiger. Therefore, this paper will serve to find out the dynamic relationships of the variables using the Efficiency Market Hypothesis (EMH) theory. The dynamic relationships will be measure using the long run and short run relationship which will be examine using the Johansen and Juselius Cointegration Test and Granger causality Test respectively. The variables of study are included the Industrial Production Index, Consumer Price Index, Real Effective Exchange Rate and Stock Index. The outcome of this paper suggests that both of the stoCK markets are infonnational ineffici~ncy.